Fiscal discipline and the cost of public dept service: some estiames for OECD countries - Silvia Ardagna; Francesco Caselli; Timothy Lane (European Central Bank (ECB), 2004)
We use a panel of 16 OECD countries over several decades to investigate the effects of government debts and deficits on long-term interest rates. In simple static specifications, a one-percentage-point increase in the primary deficit relative to GDP increases contemporaneous long-term interest rates by about 10 basis points. In a vector autoregression (VAR), the same shock leads to a cumulative increase of almost 150 basis points after 10 years. The effect of debt on interest rates is non-linear: only for countries with above-average levels of debt does an increase in debt affect the interest rate. World fiscal policy is also important: an increase in total OECD-government borrowing increases each country's interest rates. However, domestic fiscal policy continues to affect domestic interest rates even after controlling for worldwide debts and deficits.
Keywords: E62; E44; H62; 330; Governement deficit; long-term interest rates; public debt; Öffentliche Schulden; Haushaltsdefizit; Zins; VAR-Modell; Schätzung; OECD-Staaten